Report of Sugar-Sweetened Beverages Offered in Pennsylvania Childcare Centers. (June 2016) - Lutzkanin, Kristen M.; Myers, Abigail K.; Schaefer, Eric W.; Sekhar, Deepa L.
The study objective was to quantify sugar-sweetened beverage (SSB) offerings to children in Pennsylvania (PA) childcare centers and determine whether this information is communicated to parents. In October 2014, a SurveyMonkey link was sent to 4461 PA childcare centers. The 518 respondents represented 88% of PA counties. 279 centers (54%) serve SSBs. 330 (65%) of childcare centers provide parents a report of their child's daily intake. Of 185 centers serving SSBs and providing a daily intake report, 91% include SSB consumption. In total, 38% of centers (103/272) offer but do not report SSB consumption. In 96% of centers, parents may request their child not receive SSBs. In conclusion, though more than half of PA childcare centers surveyed offer SSBs, those providing daily intake reports usually include SSB consumption. Requiring daily intake reports may be a strategy to increase parental awareness of items consumed outside the home.